Respuesta :

Answer:

m=3

Step-by-step explanation:

Move all terms that don't contain  m  to the right side and solve.

loveuV

Answer:

m=3

Step-by-step explanation:

Simplifying

18 = 5m + 3

Reorder the terms:

18 = 3 + 5m

Solving

18 = 3 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.

18 + -5m = 3 + 5m + -5m

Combine like terms: 5m + -5m = 0

18 + -5m = 3 + 0

18 + -5m = 3

Add '-18' to each side of the equation.

18 + -18 + -5m = 3 + -18

Combine like terms: 18 + -18 = 0

0 + -5m = 3 + -18

-5m = 3 + -18

Combine like terms: 3 + -18 = -15

-5m = -15

Divide each side by '-5'.

m = 3

Simplifying

m = 3

hope this helps

ACCESS MORE